MANAGEMENT INFORMATION AND EVALUATION SYSTEM (MIES) - A STRUCTURED COST PLANNING AND CONTROL TOOL - Coral, Eliza; Possamai, Osmar; Selig, Paulo Mauricio; Kraemmer, Tania (Anais do Congresso Brasileiro de Custos - ABC)
This paper presents a model for a management information system that offers cost and efficiency measures of processes, activities and products, which is a powerful tool for planning the companys future change and controlling the day to day operation. MIES (Management Information and Evaluation System) is a management tool to structure the organization Data aiming to support the decision making process when cost information is needed. It is based on the UEP (Product Effort Unit) Cost System and ABC (Activity Based Costing) concepts. This model proposes a system that integrates all areas in the organization supporting each decision making levels for its different purposes. It can be used for planning, prevention through simulations, controlling operations and efficiency on monthly basis as well as checking the economic results of projects. Furthermore, MIES is not designed to be used independently, but as a tool for problem solving projects, Quality Control Circles, Total Quality Management or any other improvement methodology, helping the decision making process by offering economic data.